A proposed training program for the applied students at mathematics department and its impact on their teaching performance - Jabbar Faris, Ilham (Opción, 2019)
The current research aims to study the effect of a proposed training program for the applied students and their impact on their teaching performance. The sample of 73 students of the fourth stage in the mathematics department at the Faculty of Education / Ibn al-Haytham / morning study were randomized to the two experimental groups (37) (36) students. In order to achieve the objectives of the research, a training program was prepared in which a number of activities and training were carried out over a period of 15 weeks at 3 hours per session. A note card was prepared for the teaching performan- ce and by using a statistical test. Statistically among the research groups and for the benefit of the experimental group in teaching performance.